Early futsal experience and soccer tactical performance: A comparative study in brazilian players - Legnani, Elto; Cunha Neto, Pedro Sotero; Api, Gustavo; Denis, Ricardo Silva; Oliveira, Lucas Martins; Foschiera, Diogo Bertella; Legnani, Rosimeide Francisco dos Santos (Journal of Physical Education (Maringá), 2025)
Futsal practice could influence soccer skills due to adoption of constraints enhancing adaptation and leading to a better performance. However, little is known about early futsal practice on later soccer tactical knowledge. A cross-sectional study was conducted to verify the association between early futsal experience and tactical knowledge in soccer. Seventy-one soccer players were assessed regarding soccer and futsal experience, starting age, player ranking and position. A sports history questionnaire was applied, along with assessment of declarative tactical (DTK) and procedural (PTK) knowledge in match. Official matches were selected for PTK analysis, subdivided into actions performed (PAM) and not performed (NPAM) per minute and offensive tactical principles. No differences were found for any independent variable regarding futsal experience or competition level with the DTK and PTK in soccer, without correlation between both. There was a significant difference for “Club Rank” (p<0.05) favoring Rank A in PTK and PAM, however, for DTK in the overall sample (71), Rank C presented higher scores, which differences were no longer found in the subsample (29) (p=0.078). We suggest that earlier futsal experience does not mediate a better soccer tactical performance later on. Future studies should assess tactical performance concerning player perceived competence.